2015
DOI: 10.1016/j.bjid.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk of vancomycin-resistant enterococci bloodstream infection among patients colonized with vancomycin-resistant enterococci

Abstract: In conclusion, our study found that 1.55% of vancomycin-resistant enterococci-colonized children had developed vancomycin-resistant enterococci bloodstream infection among the pediatric intensive care unit and hematology/oncology patients; according to our findings, we suggest that immunosupression is the key point for developing vancomycin-resistant enterococci bloodstream infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
2
18
1
2
Order By: Relevance
“…14 Previous studies have evaluated the predictive value of VRE screening swabs in forecasting the prevalence of VRE among all causes of bacterial infection. [15][16][17][18][19] In this study, we sought to investigate the utility of results obtained with VRE screening swabs in predicting vancomycin resistance among subsequent sterile-site infections with Enterococcus. We hypothesized that among patients with sterile-site Enterococcus infections, prior positive results with VRE screening swabs would reliably predict vancomycin resistance, but prior negative results would not reliably rule out vancomycin resistance.…”
mentioning
confidence: 99%
“…14 Previous studies have evaluated the predictive value of VRE screening swabs in forecasting the prevalence of VRE among all causes of bacterial infection. [15][16][17][18][19] In this study, we sought to investigate the utility of results obtained with VRE screening swabs in predicting vancomycin resistance among subsequent sterile-site infections with Enterococcus. We hypothesized that among patients with sterile-site Enterococcus infections, prior positive results with VRE screening swabs would reliably predict vancomycin resistance, but prior negative results would not reliably rule out vancomycin resistance.…”
mentioning
confidence: 99%
“…E, quando se refere ao óbito ocorrido em pacientes que desenvolveram IRAS, essa taxa poderá chegar a 70%. 13 Em uma pesquisa realizada na UTI do Complexo Hospitalar Mangabeira Governador Tarcísio Burity, localizado no município de João Pessoa-PB, dos pacientes analisados 51,6% eram do sexo masculino; em relação ao tipo de internação 57,4% foram indicações clínicas; quanto a procedência 38,9% foram procedentes de outras unidades do hospital; o tempo médio de permanência na UTI foi de 9,18 dias, o que diverge com os dados encontrados no presente estudo; e no que se refere à faixa etária, 52% estavam acima de 65 anos. Este dado corrobora com esta pesquisa.…”
Section: Resultsunclassified
“…In a study performed by Ostrowski et al, prevalence of VRE colonization in surgical intensive care unit was found as 12% and organ transplantation was defined as a risk factor 18 . When reasons of the hospitalization were analyzed in our patient groups; number of the patients who were admitted to the intensive care unit with internal reasons was found to be higher than the other causes.…”
Section: Discussionmentioning
confidence: 99%